2018
DOI: 10.1111/hsc.12672
|View full text |Cite
|
Sign up to set email alerts
|

Talking about overweight and obesity in rural Australian general practice

Abstract: As many patients’ sole point of contact with the health care system, primary health care physicians (general practitioners [GPs] in Australia) are often positioned as key players in responding to rates of overweight and obesity in dominant public discourse. However, research from Western industrialised countries suggests that GPs may not be prepared for, or confident in, having conversations about overweight and obesity with patients. Little attention has been given to this topic in Australia, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…For participants, integrating social justice into clinical practice meant understanding individual health behaviours related to weight and otherwise as bounded by broader social conditions, while recognising that people had situated agency to improve their wellbeing in the face of external challenges. These findings align with prior research by Malatzky and Glenister (2019), who found that GP participants eschewed dominant individualistic approaches to weight. Unfortunately, research shows that the personal responsibility for health discourse still exerts power on larger patients, who experience self‐blame because of their weight status (Lewis et al., 2011; Thomas et al., 2008).…”
Section: Discussionsupporting
confidence: 91%
“…For participants, integrating social justice into clinical practice meant understanding individual health behaviours related to weight and otherwise as bounded by broader social conditions, while recognising that people had situated agency to improve their wellbeing in the face of external challenges. These findings align with prior research by Malatzky and Glenister (2019), who found that GP participants eschewed dominant individualistic approaches to weight. Unfortunately, research shows that the personal responsibility for health discourse still exerts power on larger patients, who experience self‐blame because of their weight status (Lewis et al., 2011; Thomas et al., 2008).…”
Section: Discussionsupporting
confidence: 91%
“…This was associated with not offending patients due to the stigmatised nature of obesity. These findings share similarities with previous literature both urban practice based 22,24 and rural practice based 34,35 which identify barriers to include time constraints, avoiding offensive or stigmatising language, and the need to not jeopardise the therapeutic relationship. However, this study found additional barriers to communication that extend previous literature.…”
Section: Discussionsupporting
confidence: 87%
“…22,23,26,30,31 Some rural-only-based Australian studies indicated that GPs experience communication difficulties when discussing weight in general practice and face challenges when delivering obesity health care. 34,35 However, there is limited understanding of the weight management barriers faced by rural GPs in NZ, specifically, in the rural Waikato region which has a significant Māori population. 36 While the Clinical Guidelines for Weight Management (CGWM) in adults 11 indicates that GPs are positioned as best suited to manage obesity in their clinical practice, obesity is still a major health concern indicating there could be barriers within this space hindering weight management efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term family practice is used in this publication as this term has wider recognition from an international perspective. Participants attending primary care view their family medical practitioner (FP) and family practice nurse (FPN) as having a key role in managing obesity [ 4 , 5 ]. We know from previous research however that within this setting weight, body mass index (BMI) and waist circumference (WC) are infrequently assessed [ 6 8 ], and opportunities to provide comprehensive weight management advice is often missed [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%